Pemberdayaan Masyarakat Tani Ternak Berbasis Produk Olahan Pakan Fermentasi di Desa Cemara Jaya, Kabupaten Halmahera Timur: Empowerment of Livestock Farming Communities Based on Fermented Feed Products in Cemara Jaya Village, East Halmahera Regency - Hariyono, Dwi Nur Happy; Saelan, Emy (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Cemara Jaya in Wasile District has the potential for developing the livestock sector, especially cattle. However, breeders face several obstacles, that is, feed is abundant in the rainy season and less in the dry season. In addition, several community-owned cattle had low body condition scores and thus, an effort is needed to increase livestock productivity through appropriate counseling and training. This service activity aimed to empower the community through training in fermented feed processing in Cemara Jaya Village, Wasile District, East Halmahera Regency, in June-August 2024 using a participatory learning and action (PLA) approach. The stages consisted of location surveys and problem identification, training and practice, as well as monitoring and evaluation. This service activity was successfully attended by 10 breeders. This training activity began with the delivery of materials related to good cattle management, and continued with the introduction and practice of fermented feed processing. In general, this service activity had a positive impact on breeders, because they become more understanding and skilled in cattle farming, especially in the use of forage into fermented feed to increase the productivity of their livestock. Farmers were also able to practice processing fermented feed independently. It can be concluded that this service activity is able to empower farmers while increasing the knowledge and skills of farmers, especially how to process fermented feed.